LATAR BELAKANG PERPINDAHAN LOKASI PUSAT-PUSAT KERAJAAN BANJAR - Susanto, Nugroho Nur (Balai Arkeologi Kalimantan Selatan, 2007)
General of center the Royal to selected because of ease to corpe or strategic. The are as center of command activity and state owned. But , situation in the center the royal of Banjaris deferent. Bacause to anticipation the attack penetrasion of Duck military and politic. After in he year 1612 when Duck to atackt Kuin. Center of capital Royal Banjar to moved in Batang Mangapan, later to Batang banyu or Teluk Selong, later to Martapura, later to Karang lntan, and later to moved Martapura again. In the 1859 palace of Banjar in Mattapura to burning by Duck angd declared erasing inmapRoyal Kalimantan. Opposition to straight in state separate Pegustian. Center of state in so far in the Man awing river, Muara Teweh.